Neuromuscular electrical stimulation training induces myonuclear accretion and hypertrophy in mice without overt signs of muscle damage and regeneration - Aurélie Fessard; Aliki Zavoriti; Natacha Boyer; Jules Guillemaud; Masoud Rahmati; Peggy Del Carmine; Christelle Gobet; Bénédicte Chazaud; Julien Gondin (Skeletal Muscle)
Abstract Background Skeletal muscle is a plastic tissue that adapts to increased mechanical loading/contractile activity through fusion of muscle stem cells (MuSCs) with myofibers, a physiological process referred to as myonuclear accretion. However, it is still unclear whether myonuclear accretion is driven by increased mechanical loading per se, or occurs, at least in part, in response to muscle injury/regeneration. Here, we developed a non-damaging protocol to evaluate contractile activity-induced myonuclear accretion/hypertrophy in physiological conditions. Methods Contractile activity was generated by applying repeated electrical stimuli over the mouse plantar flexor muscles. This method is commonly referred to as NeuroMuscular Electrical Simulation (NMES) in Human. Each NMES training session consisted of 80 isometric contractions delivered at ∼15% of maximal tetanic force to avoid muscle damage. C57BL/6J male mice were submitted to either a short (i.e., 6 sessions) or long (i.e., 12 sessions) individualized NMES training program while unstimulated mice were used as controls. Histological investigations were performed to assess the impact of NMES on MuSC number and status, myonuclei content and muscle tissue integrity, typology and size. Results NMES led to a robust proliferation of MuSCs and myonuclear accretion in the absence of overt signs of muscle damage/regeneration. NMES-induced myonuclear accretion was specific to type IIB myofibers and was an early event preceding muscle hypertrophy inasmuch as a mild increase in myofiber cross-sectional area was only observed in response to the long-term NMES training protocol. Conclusion We conclude that NMES-induced myonuclear accretion and muscle hypertrophy are driven by a mild increase in mechanical loading in the absence of overt signs of muscle injury.